Developments in the field of allergy in 2012 through the eyes of Clinical & Experimental Allergy. Issue 12 (December 2013) - Mari, A.; Antonietta Ciardiello, M.; Passalacqua, G.; Vliagoftis, H.; Wardlaw, A. J.; Wickman, M
Summary In 2012, we received 683 submissions and published 20 editorials, 38 reviews, 11 letters and 128 original articles. This represents an acceptance rate for original papers in the range of 20%. About 30% of original papers were triaged not to go out to review, either because the editors did not feel they had sufficient priority for publication or because the topic did not feel right for the readers of the journal. We place great emphasis on obtaining sufficient high‐quality reviews to make our decisions on publication fair and consistent. Inevitably, however, there is a degree of luck about what gets published and which papers miss out, and we are always happy to receive an appeal on our decisions either at the triage stage or after review. This gives us the opportunity to revisit the decision and revise it or explain in more detail to the authors the basis for the decision. Once again in 2012, we were delighted by the quality of the papers submitted and the breadth and depth of research into allergic disease that it revealed. The pattern of papers submitted was similar in previous years with considerable emphasis on all aspects of asthma and rhinitis. We were particularly pleased with our special issue on severe asthma. Elucidating mechanisms using either animal models or patients has always been a major theme of the journal, and the excellent work in these areas has been summarized by Harissios Vliagoftis with a particularly interesting section on early‐life events guiding the development of allergic disease, which understandably continue to be a major theme of research. Magnus Wickman summarized the papers looking at the epidemiology of allergic disease including work from birth cohorts, which are an increasingly rich source of data on risk factors for allergic disease, and two papers on the epidemiology of anaphylaxis. Giovanni Passalacqua discussed the papers in the clinical allergy section of the journal, and Adriano Mari who runs the excellent Allergome website discussed the papers looking at allergens including characterization and the relative usefulness of allergen arrays versus single extracts in diagnosis and management.